1980
DOI: 10.1046/j.1537-2995.1980.20280169956.x
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effectiveness and Safety of Outdated Human Red Blood Cells Rejuvenated to Restore Oxygen Transport Function to Normal, Frozen for 3 to 4 Years at −80 C, Washed, and Stored at 4 C for 24 Hours Prior to Rapid Infusion

Abstract: Human red blood cell concentrates with hematocrit values of 75 V% were prepared from citrate-phosphatedextrose (CPD) blood, stored at 4 C for 20 to 28 days, and biochemically modified with a solution containing pyruvate. inosine, glucose, phosphate, and adenine (PIGPA Solution A). The rejuvenated red blood cells were frozen with 40% W/V glycerol in a polyolefin plastic bag and were stored at -80 C. After three to four years of frozen storage, the units were thawed, washed, and stored at 4 C in a sodium chlorid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1980
1980
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…These cells were then stored for up to 72 h in a salt buffer solution (sodium chloride and glucose, or sodium chloride, glucose and phosphate) . In vivo studies demonstrated excellent red cell recovery and 24‐h survival rates, 90% and 75%, respectively, after 1·5 years of storage and similar rates even after 3 years of storage . Further studies demonstrated that this technique could be refined with improved collection bag design and processes for glycerolization, thawing and deglycerolization , could be applied to small transfusion volumes and had theoretical benefits in extracorporeal circuits due to the impact on reducing haemolysis .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These cells were then stored for up to 72 h in a salt buffer solution (sodium chloride and glucose, or sodium chloride, glucose and phosphate) . In vivo studies demonstrated excellent red cell recovery and 24‐h survival rates, 90% and 75%, respectively, after 1·5 years of storage and similar rates even after 3 years of storage . Further studies demonstrated that this technique could be refined with improved collection bag design and processes for glycerolization, thawing and deglycerolization , could be applied to small transfusion volumes and had theoretical benefits in extracorporeal circuits due to the impact on reducing haemolysis .…”
Section: Resultsmentioning
confidence: 99%
“…These cells were then stored for up to 72 h in a salt buffer solution (sodium chloride and glucose, or sodium chloride, glucose and phosphate) [27,28]. In vivo studies demonstrated excellent red cell recovery and 24-h survival rates, 90% and 75%, respectively, after 1Á5 years of storage [29] and similar rates even after 3 years of storage [30]. Further studies demonstrated that this postsurgery.…”
Section: Rejuvenation-freeze-thaw-deglycerolizationmentioning
confidence: 94%
“…Our laboratory has reported on the biochemical modification of RBC concentrates prepared from ACD, CPD, CPDA‐1, CPDA‐2, and CPDA‐3 blood by use of a solution containing pyruvate, inosine, phosphate, and adenine 1–10 . In our previous studies, the RBCs in the various anticoagulants were stored at 4°C for different periods and treated with a solution containing pyruvate, inosine, phosphate, and adenine to increase the RBC ATP, DPG, and p50 levels.…”
mentioning
confidence: 99%
“…108,109 The RBCs are centrifuged to separate the rejuvenating solution, which is then expressed into a transfer bag and discarded.…”
Section: Rejuvenated Red Blood Cellsmentioning
confidence: 99%